Pengaruh Leverage dan Ukuran Dewan Direksi Terhadap Pengungkapan CSR - Rahmatullaili Ramadhani; Dwila Maresti (Universitas Batanghari Jambi, 2021)
This study aims to determine the influence of leverage variables and board size on disclosure of social responsibility (CSR). This research is a quantitative research. The sample used is companies that are included in LQ 45 which are listed on the Indonesia Stock Exchange in 2019. The results of this study show that leverage and board size have an effect on CSR disclosure.